2015
DOI: 10.1371/journal.pone.0124833
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Distinctively Modulate the CFTR Channel with Possible Implications in Lung Development and Transition into Extrauterine Life

Abstract: During fetal development, the lung is filled with fluid that is secreted by an active Cl- transport promoting lung growth. The basolateral Na+,K+,2Cl- cotransporter (NKCC1) participates in Cl- secretion. The apical Cl- channels responsible for secretion are unknown but studies suggest an involvement of the cystic fibrosis transmembrane conductance regulator (CFTR). CFTR is developmentally regulated with a high expression in early fetal development and a decline in late gestation. Perinatal lung transition is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 61 publications
1
16
1
Order By: Relevance
“…We recently showed in male elite soccer players that basal cortisol (directly) and the testosterone/cortisol ratio (inversely) may influence sweat rate and Na + loss during a 90-min soccer practice [10]. This association was supported by in vitro and animal model studies in which cortisol [11] and testosterone [12] were shown to regulate the CFTR protein. With regards to sweat rate and sweat Na + loss during training or match-play in elite women soccer players, only two published studies exist showing interindividual variations [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed in male elite soccer players that basal cortisol (directly) and the testosterone/cortisol ratio (inversely) may influence sweat rate and Na + loss during a 90-min soccer practice [10]. This association was supported by in vitro and animal model studies in which cortisol [11] and testosterone [12] were shown to regulate the CFTR protein. With regards to sweat rate and sweat Na + loss during training or match-play in elite women soccer players, only two published studies exist showing interindividual variations [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…To date, little is known about the effect of hormones on CFTR function, which appears to differ between the distal and the proximal airways. Our previous study showed that GCs reduced CFTR expression and activity in distal lung epithelial cells, which are responsible for gas exchange and fluid absorption [ 9 ]. In contrast, GCs stimulated CFTR activity in the air conducting proximal airways, which are responsible for MCC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that the decrease in CFTR expression was more pronounced in the caesarean than vaginal group. This was somewhat unexpected, as glucocorticoids reduce CFTR expression in vitro and in rat lungs in a dose‐dependent manner . Also, stress hormones’ – cortisol and catecholamines – concentrations in human cord blood are markedly higher in vaginal than caesarean births .…”
mentioning
confidence: 99%
“…The foetal lung is filled with fluid as a result of the active ion transport towards the alveolar lumen, thereby promoting early lung development . In late gestation and the perinatal period, the transition to extrauterine life requires a switch from fluid secretion to absorption.…”
mentioning
confidence: 99%
See 1 more Smart Citation